Management of innovation in Singaporean High-technology Small and Medium Enterprises (SMEs). - Zheng, Haoying. (2008)
The study aims to look at the strategic and organizational factors associated with the innovation behaviors in Singaporean technology-based small and medium enterprises (SMEs). Both qualitative and quantitative data were gathered and studied for this research.